How to Catch Customers’ Attention? A Study on the Effectiveness of Brand Social Media Strategies in Digital Customer Engagement - Liu, Yuying; Liu, Xinxin; Wang, Meng; Wen, Decheng (Frontiers in Psychology, 2021)
Enterprises often post branded content on social media and adopt a proactive response approach to improve digital customer engagement to gain a competitive advantage. However, there are many brands which fail to operate social media as effectively as expected. The effective use of brand social media strategies to improve digital customer engagement remains an ongoing challenge for the enterprises. Based on firm-generated content theory and social presence theory, this study aims to identify the impact of brand social media strategies on different levels of digital customer engagement, including positive filtering, cognitive and affective processing as well as advocacy from content strategy and response strategy. Based on 1,519 brand posts on the official Weibo pages of eight of the top 500 Chinese brands in 2021, this study uses a multiple linear regression model to examine the impact of brand social media strategies on digital customer engagement and the moderating effects of brand image and discretionary purchases. The findings show that, on the one hand, among the brand social media content strategies, action content strategy is associated with higher levels of digital customer engagement. On the other hand, different brand social media response strategies have a differential impact on digital customer engagement levels, with cohesive response being the best strategy for increasing digital customer engagement level. In addition, the effectiveness of brand social media response strategy in digital customer engagement is further moderated by the brand image and discretionary purchases. In contrast, the effectiveness of brand social media response strategy in digital customer engagement is stronger when the brand image emphasizes its “competence” or the discretionary purchases focus on “material purchases”. This study not only enriches the research on digital customer engagement but also provides a reference for the brand strategy selection, design and management based on social media.